Fatigue Crack Propagation Behavior of RC Beams Strengthened with CFRP under High Temperature and High Humidity Environment - Dongyang Li; Peiyan Huang; Guang Qin; Xiaohong Zheng; Xinyan Guo (International Journal of Polymer Science)
Numerical and experimental methods were applied to investigate fatigue crack propagation behavior of reinforced concrete (RC) beams strengthened with a new type carbon fiber reinforced polymer (CFRP) named as carbon fiber laminate (CFL) subjected to hot-wet environment. J-integral of a central crack in the strengthened beam under three-point bending load was calculated by ABAQUS. In finite element model, simulation of CFL-concrete interface was based on the bilinear cohesive zone model under hot-wet environment and indoor atmosphere. And, then, fatigue crack propagation tests were carried out under high temperature and high humidity (50°C, 95% R · H) environment pretreatment and indoor atmosphere (23°C, 78% R · H) to obtain a-N curves and crack propagation rate, da/dN, of the strengthened beams. Paris-Erdogan formula was developed based on the numerical analysis and environmental fatigue tests.